Influence of lysine and methionine supplementation to two levels of dietary protein on performance and carcass traits of growing-finishing pigs - Phuah, C. H.; Hutagalung, R. I. (Institut Penyelidikan dan Kemajuan Pertanian Malaysia, 1980)
Fifty.four crossbreed barrows were used to study the effect of graded levels of lysine (0.70. O.HS and ~o) and methionine (0.35. O.SO and 0.650/0) in combination with two levels of protein (IS and 1200). The dietary treatments were in a 2 x 3 x 3 factorial arrangement. lysine and methionine supplementation above the normal requirement had little overall effect on rate and efficiency of liveweight gain. An increase of methionine in a ISIr. protein diet resulted in a linear (PI..O.01) reduction in daily gain and feed intake. Carcass parameters were not significantly affected by lysine and methionine levels in diets. However. there was a tendency for chilled dressed weight to decrease with increasing dietary methionine and to increase with increasing lysine. Lysine and methionine had little overall effect on backfat thickness of the pigs. while the cross-sectional area of 1. dorsi was slightly decreased by addition of lysine but increaed by addition of methionine. Carcasses were significantly (PI..O.01) longer from pigs given higher concentration of lysine.